2001
DOI: 10.1097/00007890-200106150-00011
|View full text |Cite
|
Sign up to set email alerts
|

??4 Integrin in Islet Allograft Rejection1

Abstract: These data show that alpha4 integrin is critically important to allograft rejection. Anti-VCAM-1 antibody appears to prevent rejection without qualitatively affecting either T cell activation or migration to the graft. Conversely, anti-alpha4 integrin antibody and CS1-peptide may prevent islet allograft rejection by altering either T cell activation or lymphocyte trafficking. Blocking interactions between alpha4 integrin and its ligands may provide novel forms of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The reason for the lack of effect of CS1 peptide on either the degree of insulitis or the onset of diabetes is unclear but the difference may be that in the islet allograft setting the lymphocytes are not activated at the beginning of treatment while in the autoimmune diabetes setting the lymphocytes are already activated. Similarly, we have previously shown that treatment with mAbs against a4-integrin (PS/2) prevents in vitro responses to alloantigen [20]. Other studies have suggested that other mAbs against a4-integrin (R1.2) do not block in vitro responses to islet antigens [8].…”
Section: Groupsupporting
confidence: 57%
See 1 more Smart Citation
“…The reason for the lack of effect of CS1 peptide on either the degree of insulitis or the onset of diabetes is unclear but the difference may be that in the islet allograft setting the lymphocytes are not activated at the beginning of treatment while in the autoimmune diabetes setting the lymphocytes are already activated. Similarly, we have previously shown that treatment with mAbs against a4-integrin (PS/2) prevents in vitro responses to alloantigen [20]. Other studies have suggested that other mAbs against a4-integrin (R1.2) do not block in vitro responses to islet antigens [8].…”
Section: Groupsupporting
confidence: 57%
“…Therefore, the in vivo effects of adhesion molecule blockade, with monoclonal antibodies or with peptide inhibitors, may be quite complex. We previously have shown that treatment with CS1 peptide prevents islet allograft rejection in mice by preventing lymphocyte homing to the graft [20]. The reason for the lack of effect of CS1 peptide on either the degree of insulitis or the onset of diabetes is unclear but the difference may be that in the islet allograft setting the lymphocytes are not activated at the beginning of treatment while in the autoimmune diabetes setting the lymphocytes are already activated.…”
Section: Groupmentioning
confidence: 99%
“…Donor Balb/c islets were transduced with either Ad-XIAP or Ad-LacZ and transplanted under the kidney capsule of CBA recipients. Remarkably, only the XIAPexpressing islet transplants were found to persist beyond the normal range for islet allograft rejection of 10 -24 days in this model (21). In fact, 9 of 10 recipients of XIAPexpressing islet allografts maintained normoglycemia until the animals were killed between days 45 and 72 posttransplant (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…In an experimental autoimmune encephalomyelitis model, MK1.9 reduced disease severity (54). Another VCAM-1 Ab, MK2.7, allowed long-term islet allograft survival of .100 d with a survival rate of 75% of the islet grafts (55). In a mouse model of Crohn's disease, MK2.7 treatment yielded a 70% resolution of the acute inflammation (56).…”
Section: Discussionmentioning
confidence: 99%